Equitable access to COVID-19 vaccine distribution - the case of the Andean Community - Cadillo Chandler Dhanay; Nuottila Jouko; Ballardini Rosa Maria (Sage, 2025)
The COVID-19 pandemic has shown how equitable vaccine distribution still remains unaccomplished. While access to COVID-19 vaccines has been efficient in the EU, the Latin American situation is very different. For example, the Andean Community reports that, as of December 2022, 83% of the population had received at least the first dose of the vaccine while only 43% had received the third dose (http://www.orasconhu.org). Motivated by the challenges and successes endured by countries in the Andean Community vis-à-vis the EU during COVID-19 vaccine roll-outs, we analyse key legal, policy and management factors affecting vaccine equity. We are especially critical of the strategy followed in the Andean Community, namely, of increasing dependency on imports and donations instead of harnessing other more effective policies. We highlight the specific role of the factors identified in achieving coherent policy strategies and propose recommendations to promote equitable vaccine distribution in the Andean Community, and beyond.